The accuracy of clinical diagnosis for dehydration according to the integrated management of childhood illness - Siswanto Marudut; Yati Soenarto; Mohammad Juffrie (Paediatrica Indonesiana, 2006)
Background Acute diarrheal disease causes over 5 milion deathsworldwide in children under 5 years old, mostly because of failureto detect and treat dehydration properly and immediately.Objective To determine the validity of clinical diagnosis of dehy-dration according to Integrated Management of Childhood Illness(IMCI) as a diagnostic test for dehydration in children under fiveyears old.Methods A prospective observational study was done for clinicaldiagnosis in dehydration. Children aged 2 months-5 years old withdiarrhea and or vomiting who visited the primary health centers inYogyakarta were enrolled. Clinical diagnosis was made by atrained IMCI nurses. Dehydration was defined as the presence ofdecreasing consciousness, very sunken eyes, slow reaction whenoffered a drink, and decreased skin elasticity. Ninety-five per-cents confidence intervals (CI) were calculated, and the signifi-cance was assessed by X 2 .Results There were 148 children aged 2 months to 5 years oldenrolled this study. Clinical dehydration used according to IMCIproduced sensitivity of 91% (95% CI 83;98), specificity of 82%(95% CI 75;89), positive predictive value (PPV) of 70% (95% CI58;77), negative predictive value (NPV) of 94% (95% CI 90;98),positive likehood ratio of 5.17 (95% CI 3.37;7.94), and negativelikehood ratio of 0.11 (95% CI 0.04;0.27).Conclusion Clinical diagnosis for dehydration according to IMCIis sufficiently accurate as a diagnostic test for dehydration in chil-dren under 5 years old